The role of ALBI score in patients treated with stereotactic body radiotherapy for locally advanced primary liver tumors: a pooled analysis of two prospective studies - Gkika, Eleni; Radicioni, Gianluca; Eichhorst, Alexandra; Kirste, Simon; Sprave, Tanja; Nicolay, Nils Henrik; Fichtner-Feigl, Stefan; Thimme, Robert; Wiehle, Rolf; Brunner, Thomas B.; Grosu, Anca-Ligia (Frontiers in Oncology, 2024)
IntroductionTo evaluate the outcomes after stereotactic body radiotherapy (SBRT) for locally advanced primary liver cancer.Materials and methodsPatients with locally advanced liver cancer unsuitable for other loco-regional treatments were treated with SBRT with 50–60 Gy in 3–12 fractions in two consecutive prospective trials.ResultsA total of 83 patients were included, of whom 14 were excluded, leaving 69 evaluable patients with 74 treated lesions. A total of 50 patients had hepatocellular carcinoma (HCC), and 11 patients had cholangiocarcinoma (CCC). Approximately 76% had a Child-Pugh (CP) score of A, while 54% had an albumin–bilirubin (ALBI) score of 1. With a median follow-up of 29 months, the median overall survival (OS) was 11 months, and the progression-free survival (PFS) was 18 months. The ALBI score was an important predictor of overall survival (HR 2.094, p = 0.001), which remained significant also in the multivariate analysis. Patients with an ALBI grade of ≥1 had an OS of 4 months versus 23 months in patients with an ALBI grade of 1 (p ≤ 0.001). The local control at 1 and 2 years was 91%. Thirteen patients developed grade ≥ 3 toxicities, of whom nine patients experienced liver toxicities. Patients with a higher ALBI score had a high risk for developing hepatic failure (OR 6.136, p = 0.006).DiscussionSBRT is a very effective treatment with low toxicity and should be considered as a local treatment option in patients with HCC and CCC. Patients with a higher ALBI grade are at risk for developing toxicities after SBRT and have a significantly lower survival rate.